Survey of clinical features, pathogenesis and therapeutic options for Ebola haemorrhagic fever - Goudarzi, Mehdi; Fazeli, Maryam; Azad, Mehdi; Seyedjavadi, Sima Sadat (Archives of Advances in Biosciences, 2015)
The genus Ebola virus first was recognized in 1976, when two outbreaks occurred in Zaire and Sudan. Ebola virus disease (EVD) is a highly contagious disease that can affect both human and nonhuman primates: Zaire ebolavirus (ZEBOV), Sudan ebolavirus (SEBOV), Côte d’Ivoire ebolavirus (CEBOV), Bundibugyo ebolavirus (BEBOV) and Reston ebolavirus (REBOV) are five members of the Filoviridae family that can cause haemorrhagic fever. EVD is transmitted by direct contact with contaminated blood or other biological fluids of the infected animals such as chimpanzees, gorillas, fruit bats, monkeys, forest antelope and porcupines found ill or dead or in the rainforest. Ebola is responsible for different clinical futures that can be ranged from fever, headache, arthralgia, myalgia, abdominal pain, anorexia and vomiting to severe respiratory disorders, viral hemorrhagic fever, cardio-vascular disorders and hypovolaemic shock. Although there is no specific treatment for EVD, considerable advances like use of monoclonal antibody, intefron and Favipiravir/T-705 as effective chemotherapeutic agent in treatment of EBV have been made. To date, 25 outbreaks of EVD have been reported. Hence, EVD as a zoonotic disease should be more focused not only in endemic area but also in throughout the world. Awareness of the disease and routes of transmission and also continuous surveillance to combat disease and outbreaks is necessary.